Smallholder agriculture and food security in the City of Tshwane Municipality - Ramanyimi, N. D. (University of the Free State)
The study aims to investigates the role of smallholder agriculture contributing to food security system using resources within the area of City of Tshwane Metro municipality with special focus on the rights to agriculture resources and its value chain (markets/prices), rights to food security by assessing access food availability, food accessibility, food utilisation (meeting nutritional requirements), and food stability sustainability. The study applied a descriptive research using a mixed model approach of both qualitative and quantitative research study. A purposive sampling method was used to identify 61 smallholder agriculture farmers from a population of 412 farmers and five officials participated in the study. The main findings of the research indicate that there is a positive significant relationship between smallholder agriculture and food security as food produced is sufficient to satisfy food access to the household. The smallholder has powers to land but does not use it optimally. Further violations of rights to markets persist, especially formal markets with regard to food prices. The study concludes that the relationship has the potential to contribute to the country‟s challenges of poverty and employment and it is therefore recommended that it should be considered by giving it necessary recognition it deserves. Where necessary the relationship needs to be natured by providing good environment for it to excel e.g. establishment of small-scale financial credit facilities.
Dissertation (MDS (Development Studies))--University of the Free State, 2019
Keywords: Smallholder agriculture; Food security; Sovereignty